Metamaterial-based wearable flexible elliptical UWB antenna for WBAN and breast imaging applications - Alhawari, A.R.H. (American Institute of Physics Inc., 2021)
This paper presents a metamaterial-based flexible wearable ultra-wideband (UWB) antenna for breast imaging and wireless body area network (WBAN) applications. The wearable antenna is required to be a planar and low-profile structure using flexible materials. The proposed antenna comprises two layers of denim (10 Ã 10 mm2) and felt (10 Ã 15 mm2). The antenna was integrated with six metamaterial unit cells using a modified grain rice shape within a split ring resonator to enhance the bandwidth, gain, and directivity and reduce the specific absorption rate value to less than 2 W/kg. The proposed antenna operates within a broad bandwidth range (6.5 GHz-35 GHz) with the maximum gain and directivity of 8.85 dBi and 10 dBi, respectively, and a radiation efficiency of more than 70 over its operating frequency band. The results verified good agreement between the simulation and measurement of the proposed technique in detecting an existing tumor with a diameter of 4 mm from any location inside the breast. The results convincingly proved the capability of the proposed wearable UWB antenna system for both WBAN and breast imaging applications. Â© 2021 Author(s).